Single-center experience of fetus in fetu: A case series - Habachi, G; Sabolic, I; Mesic, M; Ksia, A; ben Fredj , M; ben Youssef, S; Sfar, S; Kechiche, N; Lamiri, R; Mekki, M; et al. (Journal of Neonatal Surgery, 2024)
Background: Fetus in fetu is a rare congenital malformation resulting from abnormal embryogenesis in a monochorionic diamniotic twinning gestation. This study aimed to document our experience with this anomaly in a developing country. Methods: This retrospective analysis covers cases of fetus in fetu diagnosed at our institution between 1999 and 2023. Patients presenting with an intracorporeal mass containing a vertebral column and an appropriate arrangement of organs and limbs around the axis were included in the study. Results: Five female patients with fetus in fetu were identified. The timing of diagnosis varied from incidental antenatal ultrasound discovery to postnatal abdominal mass presentation. The initial diagnosis involved radiological and serological investigations, confirmed by histopathology after surgical excision. The mean age at the time of surgery was 44 days. All patients underwent complete excision of the fetal mass, resulting in excellent postoperative outcomes and no recurrences. Conclusion: Fetus in fetu is a pediatric rarity and must be distinguished from a teratoma mass, which carries a high malignant potential. Histological and genetic studies may contribute to understanding the pathogenesis and etiology of the disease.